New insights into the origin of perylene in geological samples - Grice, Kliti; Lu, H.; Atahan, P.; Asif, Muhammad; Hallman, Christian; Greenwood, Paul; Maslen, E.; Tulipani, S.; Williford, Kenneth; Dodson, J. (Pergamon-Elsevier Science Ltd, 2009)
The origin of the polycyclic aromatic hydrocarbon (PAH) perylene in sediments and petroleum has been a matter of continued debate. Reported to occur in Phanerozoic organic matter (OM), fossil crinoids and tropical termite mounds, its mechanism of formation remains unclear. While a combustion source can be excluded, structural similarities to perylene quinonelike components present in e.g. fungi, plants, crinoids and insects, potentially suggest a product?precursor relationship. Here, we report perylene concentrations, 13C/12C, and D/H ratios from a Holocene sediment profile from the Qingpu trench, Yangtze Delta region, China. Perylene concentrations differ from those of pyrogenic PAHs, and rise to prominence in a stratigraphic interval that was dominated by woody vegetation as determined by palynology including fungal spores. In this zone, perylene concentrations exhibit an inverse relationship to the lignin marker guaiacol, D/H ratios between 284 o/oo and 317 o/oo, similar to the methoxy groups in lignin, as well as co-variation with spores from wood-degrading fungi. 13C/12C of perylene differs from that of land plant wax alkanes and falls in the fractionation range expected for saprophytic fungi that utilise lignin, which is isotopically lighter than cellulose and whole wood. During progressive lignin degradation, the relative carbon isotopic ratio of the perylene decreases. We therefore hypothesise a relationship of perylene to the activity of wood-degrading fungi. To support our hypothesis, we analysed a wide range of Phanerozoic sediments and oils, and found perylene to generally be present in subordinate amounts before the evolutionary rise of vascular plants, and to be generally absent from marine-sourced oils, few exceptions being attributed perhaps to a contribution of marine and/or terrestrial derived fungi, anoxia (especially under marine conditions) and/or contamination of core material by fungi. A series of low-molecular-weight aromatic quinones bearing the perylene-backbone were detected in Devonian and Cretaceous sediments, potentially representing precursor components to perylene.